2021
DOI: 10.1088/1361-6560/ac3840
|View full text |Cite
|
Sign up to set email alerts
|

Design and modeling of a Laue lens for radiation therapy with hard x-ray photons

Abstract: We have designed and modeled a novel optical system composed of a Laue lens coupled to an x-ray tube that produces a focused beam in an energy range near 100 keV (λ = 12.4 picometer). One application of this system is radiation therapy where it could enable treatment units that are considerably simpler and lower in cost than present technologies relying on linear accelerators. The Laue lens is made of Silicon Laue components which exploit the silicon pore optics technology. The lens concentrates photons to a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…The concept uses bent and unbent crystals and is projected to achieve a detection area of ∼600 cm 2 in the two bands from 460 keV to 522 keV and from 825 keV to 910 keV. 13,37 Finally, with regard to fabrication, we note that Wade et al have developed techniques for assembling Laue lenses with excellent results 38 (see also 39 ).…”
Section: Laue Lensesmentioning
confidence: 99%
“…The concept uses bent and unbent crystals and is projected to achieve a detection area of ∼600 cm 2 in the two bands from 460 keV to 522 keV and from 825 keV to 910 keV. 13,37 Finally, with regard to fabrication, we note that Wade et al have developed techniques for assembling Laue lenses with excellent results 38 (see also 39 ).…”
Section: Laue Lensesmentioning
confidence: 99%
“…SPO technology has also the potential to create advanced gamma-ray focusing elements via the use of diffraction in the volume of the crystalline plates. Self-standing single or double-curvature stacks of plates can be used as Laue lens elements providing improved focusing capability compared to other methods [22].…”
Section: Potential and Limitations Of Spomentioning
confidence: 99%
“…Despite the peak acceleration being outside of the specification band for some frequencies, this SRS is considered excellent, and the test successful. Adapted from [22]. optical axis, are used to assist in identifying failures, as well as their modes.…”
Section: Ruggedisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Girou and colleagues, referred to as 'the authors' in the following, in their paper (Girou et al 2021), described a new design of Laue lens and in section 4.3 compared the expected performance of the proposed lens with the results reported in our previous work (Paternò et al 2016). The authors found a significant difference between the dose rate at the focus obtained with their lens, namely 0.2 Gy min −1 , and the dose rate of about 8.6 Gy min −1 that can be obtained from the values reported in our paper, namely 2 Gy delivered in 14 s.…”
Section: Dear Sirmentioning
confidence: 99%